Effect of growth techniques on the structural and optical properties of TiO2 nanostructures. (11th January 2018) - Chacko, Levna; Aneesh, P M
Abstract: Being a promising transition metal oxide having a phase dependent wide band gap, TiO2 holds a significant place in semiconducting and flexible nanodevices. TiO2 nanoparticles have been prepared by co-precipitation and hydrothermal methods. The effect of both the synthesis technique on the structural, morphological and optical properties of TiO2 nanoparticles has been investigated. The as-prepared TiO2 nanostructures were characterized by means of x-ray diffraction, field-emission scanning electron microscopy, Raman analysis, diffuse reflectance spectroscopy and photoluminescence studies. The studies reveal that co-precipitation method results in the formation of agglomerated nanoparticles with less defects and effective luminescent property compared to the hydrothermal counterpart.